Perubahan Garis Pantai pada Musim Timur dan Barat kaitannya dengan Karakteristik Gelombang di Pesisir Kabupaten Takalar, Sulawesi Selatan - Dwi Fajriyati Inaku; Nurjannah Nurdin; Dewi Yanuarita Satari (Universitas Diponegoro, 2021)
Detection of shoreline changes needs to be done to determine changes so that supervision and management planning in a coastal area can be carried out, one of which is on the coast of Takalar Regency, South Sulawesi. This study aims to map changes in the coastline in Takalar Regency in different seasons and to see the effect of the waves on these changes. This study uses Landsat satellite imagery data from 1998-2018, and wave data obtained from Copernicus Marine Environment Monitoring Services (CMEMS). The shoreline data extraction was using the combination of single band and band ratio approach while the shoreline change rate calculation was using the Digital Shoreline Analysis System (DSAS) application. In addition, GeoDa application was used to obtain the regression analysis of the effect of waves on shoreline changes. The results showed that there were similar patterns of shoreline changes between monsoon and west monsoon, although the value were different. Coastal erosion occurs in almost all Takalar coastal area. Some areas that have a high coastal erosion value were the sub-district of South Galesong and Mappakasunggu while the areas that have a high accretion value were the sub-districts of Sanrobone, Mappakasunggu, and Mangarabombang. The waves had a significant influence on changes in shoreline in both the monsoon and west monsoon (P <0.05) with a percentage of 17,2% for the monsoon and 7.3% for the west monsoon which indicated there were other factors that influence shoreline change besides the wave factor on the Takalar Coast. Deteksi perubahan garis pantai perlu dilakukan dalam rangka pengawasan dan perencanaan pengelolaan di suatu kawasan, salah satunya di Pesisir Kabupaten Takalar, Sulawesi Selatan. Penelitian ini bertujuan untuk memetakan perubahan garis pantai di Kabupaten Takalar berdasarkan musim dan melihat pengaruh gelombang terhadap perubahan tersebut. Penelitian ini menggunakan data Citra Satelit Landsat tahun 1998-2018, dan data gelombang yang diperoleh dari Copernicus Marine Environment Monitoring Services (CMEMS). Ekstraksi data garis pantai menggunakan pendekatan perkalian single band dan ratio band sedangkan perhitungan laju perubahan garis pantai menggunakan aplikasi Digital Shoreline Analysis System (DSAS). Analisis regresi untuk melihat pengaruh gelombang terhadap perubahan garis pantai menggunakan aplikasi GeoDa. Hasil penelitian menunjukkan terdapat pola yang hampir sama antara perubahan garis pantai musim timur dan musim barat meskipun dengan besaran yang berbeda. Abrasi terjadi hampir di seluruh Pesisir Takalar. Daerah yang memiliki nilai abrasi yang tinggi yaitu Kecamatan Galesong Selatan dan Mappakasunggu sedangkan daerah yang memiliki nilai akresi tinggi yaitu Kecamatan Sanrobone, Mappakasunggu, dan Mangarabombang. Gelombang memberikan pengaruh yang signifikan terhadap perubahan garis pantai baik pada musim timur maupun barat (P<0,05) dengan persentase 17,2% untuk musim timur dan 7,3% untuk musim barat yang mengindikasikan terdapat faktor lain yang ikut mempengaruhi perubahan garis pantai selain faktor gelombang di Pesisir Takalar.